(untitled) (Discourse of Law and Administration, 2025)
The article raises the controversial issue of the legal possibility of allowing an expert to participate in the process of assessing applications for operational surveillance—either at the stage of granting consent for submitting an application to the court by authorized entities, or already during the court’s examination of such an application. The authors hypothesize that in complex cases, the prosecutor supervising operational and reconnaissance activities or the court may seek the opinion of an expert with specialized knowledge, but only if that expert holds a certificate authorizing access to classified information. The article also addresses the legal conditions under which the use of the most advanced surveillance techniques and special techniques for searching large databases may be permissible